A review of blood diseases and cytopenias associated with human parvovirus B19 infection (2015)
Parvovirus B19 is a single-stranded DNA virus which preferentially targets the erythroblast resulting in red cell aplasia, which is temporary in immunocompetent persons. Since the discovery of B19 virus in 1975, a wide variety of blood diseases and cytopenias affecting several blood cell lineages have been documented during or following B19 infection. These include cytopenias affecting the erythroid, megakaryoblastoid, myeloid and lymphoid lineages, as well as a variety of bicytopenias, pancytopenia, bone marrow necrosis / fat embolism syndrome, myelodysplastic syndrome, leucoerythroblastopenia, and hemophagocytic lymphohistiocytosis. B19 infection may also complicate and precede the course of acute leukemia, the significance of which remains to be determined. This review describes the current state of knowledge of the abnormalities of individual blood cell lineages encountered during parvovirus B19 infection, over the almost 40years since its discovery, and reveals some very interesting themes, which improve our understanding of the pathogenesis of B19 infection with particular reference to the bone marrow. © 2015 John Wiley and Sons, Ltd.